Update on the role of copanlisib in hematologic malignancies. (April 2021) - Le, Thuy; David, Jerel; Bryan, Locke J.
Clinical research in hematologic malignancies is continually advancing with emerging concepts in therapy and evolving results from clinical protocols. Targeting of the PI3K pathway remains a valuable treatment across both hematologic and solid malignancies. There are currently four United States Food and Drug Administration (FDA)-approved PI3K inhibitors, with several others in development. Copanlisib is a pan-PI3K inhibitor currently FDA-approved for the treatment of relapsed/refractory follicular lymphoma (FL) following two lines of therapy. Since FDA approval, there have been further investigations into the long-term safety profile of copanlisib, as well as treatment of FL and other lymphoma subtypes, both indolent and aggressive. Here, we review the most recent available data from clinical trials, describe the management of the most common side effects, and explore future concepts. The use of copanlisib as part of a combination therapy for various hematologic malignancies will also be discussed. Copanlisib is a unique drug compared with other PI3K inhibitors, with remarkable potential to improve our armamentarium in cancer treatment.